A generally modified cuckoo optimization algorithm for crack detection in cantilever Euler-Bernoulli beams - Moezi, Seyed Alireza; Zakeri, Ehsan; Zare, Amin (Precision engineering, 2018)
•Proposing a method for estimating location and depth of open-edge crack in cantilever Euler-Bernoulli beam.•Proposing new generally modified cuckoo optimization algorithm by applying improvements on cuckoo optimization algorithm.•Comparing the present results with ABC, PSO, COA and MCOA and researches recently performed in this field.•High accuracy of this method in estimating location and depth of a crack with much lower number of function evaluations.•Validating results obtained using modal test experiment. In this research, a new and Generally Modified Cuckoo Optimization Algorithm (GMCOA) for solving the problem of detecting and estimating open-edge cracks in cantilever Euler-Bernoulli beams is proposed. This method is generated via applying general changes to Cuckoo Optimization Algorithm (COA) and improving its performance. The performance of this algorithm is investigated by performing simulation tests on a cantilever beam. Frequency response equations of a cracked beam is modelled using Euler-Bernoulli beam method and Hamilton's principle and its results are verified via modal tests on a sample beam. Tuning parameters of this optimization procedure is determined using Taguchi design of experiments method. An objective function consisting of the difference between measured and calculated first to fourth bending natural frequencies of the cracked beam is considered for optimization. Analyzing and comparing the results obtained using this method and the results of previous researches shows a better performance for this method. This method, in addition to estimating crack depth and location more accurately than other methods, achieves this accuracy with lower number of Function Evaluations (FEs). By using this number of FEs, other methods have not found crack location and depth more accurately than this method.